2011
DOI: 10.1186/1755-8794-4-82
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA methylation changes associated with human gastric cancer

Abstract: BackgroundEpigenetic alteration of gene expression is a common event in human cancer. DNA methylation is a well-known epigenetic process, but verifying the exact nature of epigenetic changes associated with cancer remains difficult.MethodsWe profiled the methylome of human gastric cancer tissue at 50-bp resolution using a methylated DNA enrichment technique (methylated CpG island recovery assay) in combination with a genome analyzer and a new normalization algorithm.ResultsWe were able to gain a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…This finding confirms the close association between MSI and the CpG island methylator phenotype (CIMP) already described in gastric and colorectal adenocarcinomas (Toyota et al 1999, Samowitz et al 2005. In these sites, genome-wide methylation studies have confirmed that CIMP and MSI are a homogeneous subset of cancers harboring aberrant DNA methylation mechanisms (Park et al 2011, Hinoue et al 2012, Xu et al 2012. Fourthly, we demonstrated that the wellknown relationship reported in colorectal adenocarcinomas between MSI phenotype and BRAF V600E mutation (Boland et al 2009) is also found in MSI-NEC/MANECs of the colonrectum.…”
Section: Discussionsupporting
confidence: 75%
“…This finding confirms the close association between MSI and the CpG island methylator phenotype (CIMP) already described in gastric and colorectal adenocarcinomas (Toyota et al 1999, Samowitz et al 2005. In these sites, genome-wide methylation studies have confirmed that CIMP and MSI are a homogeneous subset of cancers harboring aberrant DNA methylation mechanisms (Park et al 2011, Hinoue et al 2012, Xu et al 2012. Fourthly, we demonstrated that the wellknown relationship reported in colorectal adenocarcinomas between MSI phenotype and BRAF V600E mutation (Boland et al 2009) is also found in MSI-NEC/MANECs of the colonrectum.…”
Section: Discussionsupporting
confidence: 75%
“…MIRAseq (46) MeDIP-seq (16), MethylCap-seq (using MeCP2) (8), MBD-isolated genome sequencing (49) follows more or less similar protocols (except affinity enrichment itself). As an example, two of the reported workflows are summarized in Figure 8 (46,50). Although similar in approach, enrichment methods target different compartments of the genome.…”
Section: Fig 6 An Example Of Goldengatementioning
confidence: 99%
“…Affinity enrichment coupled to high-throughput sequencing. These workflows are based on protocols reported by (42) and (46) and may differ from other reports. A portion of DNA is kept aside (input control), which is used to compare relative enrichment of methylated fraction in precipitated samples.…”
Section: Future Challengesmentioning
confidence: 99%
“…With some exceptions [35][36][37], DYRK1A and DYRK2 have been characterized as a potential tumor suppressor [38][39][40][41][42][43][44][45][46][47][48][49]. In contrast, DYRK1B (also known MIRK), closely related to DYRK1A, have been characterized as a positive regulator of cancer cell survival [50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Dual Specificity Tyrosine Phosphorylation-regulated Kinases mentioning
confidence: 99%